Carbon capture, storage and utilization a possible climate change solution for energy industry - Goel, Malti; Sudhakar, M.; Shahi, R. V. ([Place of publication not identified], CRC Press, 2018)
Carbon capture and storage (CCS) is among the advanced energy technologies suggested to make the conventional fossil fuel sources environmentally sustainable. It is of particular importance to coal-based economies. This book deals at length with the various aspects of carbon dioxide capture, its utilization and takes a closer look at the earth processes in carbon dioxide storage. It discusses potential of Carbon Capture, Storage, and Utilization as innovative energy technology towards a sustainable energy future. Various techniques of carbon dioxide recovery from power plants by physical, chemical, and biological means as well as challenges and prospects in biomimetic carbon sequestration are described. Carbon fixation potential in coal mines and in saline aquifers is also discussed. Please note: This volume is Co-published with The Energy and Resources Institute Press, New Delhi. Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka
OCLC-licensed vendor bibliographic record.
Keywords: Carbon sequestration -- India; Carbon sequestration -- Technological innovations -- India; Carbon sequestration -- Government policy -- India; Carbon dioxide -- India; Energy industries -- Environmental aspects -- India